Enhancement of norfloxacin solubility via inclusion complexation with β-cyclodextrin and its derivative hydroxypropyl-β-cyclodextrin - Gabriel Onn Kit Loh; Yvonne Tze Fung Tan; Kok-Khiang Peh (Elsevier, 2016)
The objectives of the study were to investigate the effects of β-cyclodextrin (βCD) and hydroxypropyl-β-cyclodextrin (HPβCD) on the solubility and dissolution rate of norfloxacin prepared using three different methods, at drug to cyclodextrin weight ratios of 1:1, 1:2, 1:4 and 1:8. All the methods increased the solubility and dissolution rate of norfloxacin via inclusion complexation with βCD and HPβCD. Norfloxacin was converted from crystalline to amorphous form through inclusion complexation. Solvent evaporation method was the most effective method in terms of norfloxacin solubilisation, while inclusion complex of HPβCD has higher solubility than βCD complex when prepared using the same procedure.